FRI0287 EFFICACY OF EOSINOPHILIC GRANULOMATOSIS WITH POLYANGIITIS TREATMENTS ACCORDING TO THE TYPE OF MANIFESTATIONS BASED ON ANALYSIS OF 636 PATIENTS. (June 2019) - Papo, Matthias; Sinico, Renato A.; Teixeira, Vítor; Urban, Maria-Letizia; Mahrhold, Juliane; Monti, Sara; Cassone, Giulia; Schiavon, Franco; Seeliger, Benjamin; Neumann, Thomas; Kroegel, Claus; Groh, Matthieu; et al.
Abstract : Background: Eosinophilic granulomatosis with polyangiitis (EGPA) (Churg–Strauss) is a small-vessel necrotizing vasculitis characterized by blood and tissue eosinophilia and asthma. Glucocorticoids (GCs) represent the treatment cornerstone. So far, EGPA management has been based on conventional immunosuppressants, but GC-dependence remains frequent. Recently, therapies targeting B cells and interleukin-5 have been prescribed, but data on large cohorts are lacking. Objectives: This study aimed to describe therapeutic management and efficacy of treatments in EGPA patients. Methods: We set up a multicenter European cohort that included 636 EGPA patients. Treatments used, complete remission rates and vasculitis relapse-free survival were recorded. Complete remission was defined as absence of vasculitis relapse and prednisone dose <5 mg/d at last follow-up. Efficacy to treat GC-dependent asthma/ENT signs was defined as the absence of asthma/ENT symptoms and prednisone dose ≤7.5mg/d within the 6 months after initiation. Results: For induction, cyclophosphamide (CYC) was the most frequently prescribed immunosuppressant (36.2%), more often in patients with FFS ≥1 (P<0.0001). GCs alone were used in 37.3%, azathioprine (AZA) in 14.4% and methotrexate (MTX) in 6.2%. No difference was found in the 10-years overall survival between patients with FFS=0, FFS=1 and FFS≥2. Complete remission rates were similar between conventional immunosuppressants (CYC, AZA or MTX) and GCs alone. Vasculitis relapse-free survival was also similar between CYC, AZA or MTX and GCs alone. Similar results were observed for first vasculitis relapse treatments. During follow-up, GC-dependent asthma and/or ENT manifestations were treated with AZA (40%), MTX (25%), mycophenolate mofetil (16%), rituximab (RTX) (21%), CYC (19%), cyclosporine (6%), omalizumab (5.9%) and mepolizumab (5.5%), allowing GC-tapering ≤7.5mg/in 23%, 31%, 17%, 43%, 5%, 71%, 25% and 50%, respectively. Conventional immunosuppressants were mostly used in first and second line, while eosinophil-targeted biotherapies were used in 4 th or 5 th lines. Conclusion: In EGPA patients, the response to conventional immunosuppressants, in addition to GCs, is often disappointing compared to GCs alone, without clear benefit on complete remission rates and relapse-free survival. In contrast, notwithstanding a small number of treated patients, eosinophil-targeted therapies seemed promising to treat asthma and/or ENT manifestations. Disclosure of Interests: Matthias Papo: None declared, Renato A. Sinico: None declared, Vítor Teixeira: None declared, Maria-Letizia Urban: None declared, Juliane Mahrhold: None declared, Sara Monti: None declared, Giulia Cassone: None declared, Franco Schiavon: None declared, Benjamin Seeliger: None declared, Thomas Neumann: None declared, Claus Kroegel: None declared, Matthieu Groh: None declared, Chiara Marvisi: None declared, Maxime Samson: None declared, Thomas Barba: None declared, David Jayne Grant/research support from: David Jayne has received research grants from Chemocentryx, GSK, Roche/Genentech and Sanofi-Genzyme. He has received consultancy fees from Astra-Zeneca, Boehringer-Ingelheim, Chemocentryx, Chugai, GSK, Infla-RX, Insmed and Takeda, Bernhard Hellmich Consultant for: Roche, Speakers bureau: Abbvie, MSD, Roche, Novartis, Pfizer, Carlomaurizio Montecucco Speakers bureau: AbbVie, Bristol-Myers Squibb, Celgene, Sanofi, Genzyme, Lilly, MSD, Pfizer, UCB, Carlo Salvarani Grant/research support from: Roche, Consultant for: Eli Lilly and Company, Roche, Abbvie, Jean-Emmanuel Kahn: None declared, Bernard Bonnotte: None declared, Cécile-Audrey Durel: None declared, Xavier Puéchal: None declared, Luc Mouthon: None declared, Loïc Guillevin: None declared, Giacomo Emmi: None declared, Augusto Vaglio: None declared, Benjamin Terrier: None declared